Spray‐flame synthesis of La(Fe, Co)O3 nano‐perovskites from metal nitrates. Issue 1 (6th September 2019) - Angel, Steven; Neises, Julian; Dreyer, Maik; Friedel Ortega, Klaus; Behrens, Malte; Wang, Yuan; Arandiyan, Hamidreza; Schulz, Christof; Wiggers, Hartmut
Abstract: Nano‐sized perovskites were synthesized in a spray flame from nitrate precursors dissolved in ethanol and in ethanol/2‐ethylhexanoic acid (2‐EHA) mixtures. Experiments with ethanol led to a broad particle‐size distribution and to the formation of undesired phases such as La2 CoO4, La2 O3, and Co3 O4 . The addition of 2‐EHA can initiate micro explosions of the burning droplets and has been systematically investigated toward the formation of single‐phase, high‐surface‐area LaCoO3 and LaFeO3 with a narrow size distribution. To investigate the effect of 2‐EHA, temperature‐dependent changes of the chemical composition of the precursor solutions were analyzed with ATR‐FTIR between 23 and 70°C. In all cases, the formation of esters was identified while in the solutions containing iron, additional formation of carboxylates was observed. The synthesized materials were characterized by BET SSA, XRD, SAED and EDX‐TEM and their catalytic activity was analyzed, reaching 50% CO conversion at temperatures below 160 and 300°C for LaCoO3 and LaFeO3, respectively.